Airway β-Defensin-1 Protein Is Elevated in COPD and Severe Asthma - Katherine J. Baines; Thomas K. Wright; Jodie L. Simpson; Vanessa M. McDonald; Lisa G. Wood; Kristy S. Parsons; Peter A. Wark; Peter G. Gibson (Mediators of Inflammation)
Background. Innate immune antimicrobial peptides, including β-defensin-1, promote the chemotaxis and activation of several immune cells. The role of β-defensin-1 in asthma and chronic obstructive pulmonary disease (COPD) remains unclear. Methods. Induced sputum was collected from healthy controls and individuals with asthma or COPD. β-defensin-1 protein in sputum supernatant was quantified by ELISA. Biomarker potential was examined using receiver operating characteristic curves. β-defensin-1 release from primary bronchial epithelial cells (pBECs) was investigated in culture with and without cigarette smoke extract (CSE). Results. Airway β-defensin-1 protein was elevated in COPD participants compared to asthma participants and healthy controls. Inflammatory phenotype had no effect on β-defensin-1 levels in asthma or COPD. β-defensin-1 protein was significantly higher in severe asthma compared to controlled and uncontrolled asthma. β-defensin-1 protein could predict the presence of COPD from both healthy controls and asthma patients. Exposure of pBECs to CSE decreased β-defensin-1 production in healthy controls; however in pBECs from COPD participants the level of β-defensin-1 remanied unchanged. Conclusions. Elevated β-defensin-1 protein is a feature of COPD and severe asthma regardless of inflammatory phenotype. β-defensin-1 production is dysregulated in the epithelium of patients with COPD and may be an effective biomarker and potential therapeutic target.